Microbial biosensor based on whole cell of Pseudomonas sp. for online measurement of p-Nitrophenol - Banik R.M.; Mayank; Prakash R.; Upadhyay S.N. (My University, 2025)
Whole cells of Pseudomonas sp. were employed as the primary sensing element of a microbial biosensor suitable for online estimation of p-nitrophenol based on a Clark type oxygen electrode. In this process p-nitrophenol adapted Pseudomonas cells were immobilized on the polycarbonate membrane having pore size of 0.4 μm and placed on the tip of Clark type dissolved oxygen (DO) electrode to measure the change in oxygen concentration due to degradation of p-nitrophenol and consumption of oxygen by the Pseudomonas cells. The present study was carried out, keeping in view the possible use of the biosensor for field and online measurements of p-nitrophenol. It was tried to overcome the major limitations of the microbial biosensors viz. slow response, fixed temperature and requirement of a buffered solution of fixed strength and pH by developing a p-nitrophenol adapted Pseudomonas sp. microbial biosensor in a wide range of temperature and pH. The biosensor is suitable for quantification of p-nitrophenol in the concentration range of 10-50 μM with the varying pH (7.5-8.5) and temperature (25-40 °C) in short response time (7.0 min). © 2008 Elsevier B.V. All rights reserved.